FROM MASS DEMONSTRATIONS TO DIGITAL CRITICISM: A DESCRIPTIVE COMPARATIVE STUDY OF CHANGES IN FUEL CONSUMER RESPONSES TO FUEL PRICE INCREASES IN INDONESIA FROM CONVENTIONAL MEDIA TO DIGITAL PLATFORMS, 2000–2026 - Aldirafi Gani; Dean Joshua Dotulong; Farida Yuliaty; Vip Paramarta; Kosasih (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Fuel price increases in Indonesia have long prompted public responses because fuel prices directly affect transportation costs, household expenses, purchasing power, and perceptions of economic justice. This study aims to analyze changes in fuel consumer responses to fuel price increases in Indonesia from 2000 to 2026, particularly the shift from mass demonstrations to digital criticism. This research uses a qualitative descriptive-comparative approach by examining documents, media reports, protest records, and public digital traces. The analysis compares three periods: 2000–2010, 2011–2016, and 2017–2026. The findings indicate that public responses have shifted from collective physical actions, such as demonstrations by students, labor groups, and civil society, to more dispersed digital expressions via social media comments, hashtags, memes, short videos, and online opinions. This transformation does not indicate declining public dissatisfaction, but rather a shift in the space and form of consumer expression.